Hubungan Antara Pengetahuan PenderitaTuberculosis Dan Dukungan KeluargaDengan Kepatuhan Minum Obat DiWilayah Kerja Puskesmas JekuloKabupaten Kudus - Nugroho, Adi Septian; , H.M. Abi Muhlisin, SKM., M.Kep; , Vinami Yulian, S.Kep, Ns, M.Sc (2016)
Tuberculosis is an infectious disease caused by a rod-shaped bacterium (bacillus) known as Mycobacterium tuberculosis. The tuberculosis transmission through saliva or sputum containing bacillus tuberculosis sufferers. Pulmonary tuberculosis cases tuberculosis can be cured if the patient has a good knowledge of submissive in treatment for about 6 months and is supported with a good quality of health services in the handle with pulmonary tuberculosis. This study aims to determine the relationship between knowledge of tuberculosis patients and family support with medication adherence tuberculosis in public health service of Jekulo Kudus. This research descriptive correlative with cross sectional approach. Samples were 39 patients with tuberculosis in public health service of Jekulo Kudus with saturated sampling technique. The collecting data using questionnaires were analyzed using Fisher's Exact Test. The conclusion of the study are (1) the knowledge of tuberculosis patients on the medication adherence tuberculosis majority was sufficient (54%), (2) the family support for medication adherence tuberculosis majority was sufficient (59%), (3) the adherence tuberculosis mostly non-compliance (59%), (4) there was a relationship of knowledge tuberculosis patients with medication adherence tuberculosis in public health service of Jekulo Kudus (p-value 0.003), and (5) there was a relationship of family support with medication adherence tuberculosis in public health service of Jekulo Kudus (p-value 0.039). Keywords: tuberculosis knowledge, family support, medication adherence